Vitamins and carotenoids in the dynamics of prostate gland oncogenesis - P. V. Glybochko; E. G. Zezerov; Yu. G. Alyaev; V. B. Spirichev; D. V. Butnaru; S. E. Severin; A. Z. Vinarov; N. A. Beketova; O. G. Pereverzeva; V. A. Varshavsky; E. V. Osipov; E. A. Bezrukov (Сеченовский вестник)
The content of vitamins and relative biologically active substances including the products of lipids peroxidation has been studied in the blood of 115 males -patients of Department of Urology of I.M.Sechenov First Moscow State Medical University. The patients have been divided to four groups: prostatic carcinoma (PC); high grade prostatic intraepithelial neoplasia (HG PIN) or precancer; mixed group of conditional control – low grade PIN, benign prostatic hyperplasia, chronic prostatitis or their combination; control group of healthy men without prostate pathology. Further statistically reliable diﬀerences have been found: patients with PC had lower level of antioxidants – lycopene, vitamin E and enhanced level of diene conjugates (products of lipid peroxidation); patients with HG PIN low level of vitamin C, total carotenoids and increased diene conjugates. The diﬀerence in vitamins-antioxidants levels in patients with PC and HG PIN has not been found out.